2015
DOI: 10.1097/qad.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic polymorphisms associated with nonalcoholic fatty liver disease on HIV-infected individuals

Abstract: LPPR4 and SAMM50 allelic variants are independent risk factors for FLD and steatohepatitis development, respectively, in HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
(66 reference statements)
2
15
2
Order By: Relevance
“…More studies are warranted to elucidate this issue. By contrast, the other SNPs evaluated here, linked to SAMM50 and LPPR4 genes, which were previously associated with FLD in the HIV-infected population [14], have not shown any association with cirrhosis or significant LSP in our study. Taking into account the sample size analyzed, the case-control ratio and the minor allele frequency of those genetic markers in our population, our study had a 75% and 80% power to detect OR = 2 for the study of association of SAMM50 rs738491 and LPPR4 rs12743824 polymorphisms with cirrhosis, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…More studies are warranted to elucidate this issue. By contrast, the other SNPs evaluated here, linked to SAMM50 and LPPR4 genes, which were previously associated with FLD in the HIV-infected population [14], have not shown any association with cirrhosis or significant LSP in our study. Taking into account the sample size analyzed, the case-control ratio and the minor allele frequency of those genetic markers in our population, our study had a 75% and 80% power to detect OR = 2 for the study of association of SAMM50 rs738491 and LPPR4 rs12743824 polymorphisms with cirrhosis, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously reported a lack of association between the PNPLA3 rs738409 variant and FLD in HIV/HCV-coinfected individuals [14]. Although Signelli et al found a relation of this SNP with steatosis in a small population [10], our finding has been replicated by others [8, 9].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…There are no specific studies linking microbiome dysfunction to the development of NASH in HIV-infected patients. Furthermore, there is strong evidence on the impact of hereditary component with polymorphisms for hepatic lipid regulation and insulin signalling pathways, in both the HIV-infected and general populations [57,58].…”
Section: Pathogenesismentioning
confidence: 99%
“…This may be due to the presence of multiple risk factors including high alcohol consumption, metabolic disorders driven by HIV, viral replication, and use of cART [2225]. Studies have also shown that non-alcoholic fatty liver disease (NAFLD) and fibrosis is associated with duration of HIV, persistent HIV viral replication, cART use, as well as genetic variants [2629]. As with CVD and respiratory comorbidity, these results suggest contributory effects of HIV-related factors.…”
Section: Introductionmentioning
confidence: 99%